The influence of convenience, trust, and sharia financial literacy on students' decision-making using gopay digital wallet a case study of FAI UMSU students - Permana, Dimas Dwi; Rahmayati, Rahmayati (Jurnal Ekonomi, 2024)
This study aims to comprehend the impact of Ease of Use, Trust, and Islamic Financial Literacy on Decision-Making in Using the Go-Pay Digital Wallet, with a case study focusing on students at the Faculty of Islamic Studies (FAI) at UMSU. Adopting a quantitative approach, data for this research was gathered through the distribution of questionnaires and employing the Likert scale to measure participant responses. A total of 92 participants were selected using purposive sampling. Multiple regression analysis, processed using SPSS, served as the data analysis technique. The results of the partial test (t-test) indicate that Trust, Islamic financial knowledge, and Ease of Use significantly influence users' decisions to choose Go-Pay. The findings of this study suggest that consumers' perceptions of Ease of Use, Trust, and Islamic Financial Literacy play a crucial role in their decision-making process regarding the utilization of the Go-Pay service.